2021
DOI: 10.3390/land10020136
|View full text |Cite
|
Sign up to set email alerts
|

Forest Disturbance Types and Current Analogs for Historical Disturbance-Independent Forests

Abstract: Forest classifications by disturbance permit designation of multiple types of both old growth forests and shorter-lived forests, which auto-replace under severe disturbance, and also identification of loss of the disturbance type and associated forest. Historically, fire and flooding disturbance regimes, or conversely, infrequent disturbance, produced unique forests such as disturbance-independent forests of American beech (Fagus grandifolia), eastern hemlock (Tsuga canadensis), and sugar maple (Acer saccharum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Historical forests were old-growth closed and open forests, but not successional forests (Figure 1). In addition to composition and structure, successional forests have different functions, conditions, and biodiversity than historical forests [3,31]. Indeed, some "successional" species are declining despite the presence of abundant successional forests, indicating the misattribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historical forests were old-growth closed and open forests, but not successional forests (Figure 1). In addition to composition and structure, successional forests have different functions, conditions, and biodiversity than historical forests [3,31]. Indeed, some "successional" species are declining despite the presence of abundant successional forests, indicating the misattribution.…”
Section: Discussionmentioning
confidence: 99%
“…Open forests of fire-tolerant oaks dominated the central region, with localized forests of shade-tolerant American beech (Fagus grandifolia, about 5% of all trees), sometimes in conjunction with eastern hemlock Land 2022, 11, 161 2 of 9 (Tsuga canadensis) or sugar maple (Acer saccharum), which have similar traits of shade tolerance and a long lifespan. Beech forests were disturbance independent (i.e., old-growth with rare overstory and understory disturbances), but open oak and pine forests were also old-growth forests with long-lived species due to infrequent overstory disturbance [3]. Although the historical surveys may suffer from measurement bias, for example, a preference for American beech that may be over-representative in records, open oak and pine forest types maintained by low-severity surface fires, modulated by native human management, consistently emerge from the work of countless surveyors and are upheld by pollen evidence [4] and historical accounts that remain similar, regardless of location or date [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Without an explicit lower diameter limit, any cited density is indefinite because including smaller trees will always increase that density. In various PLS studies, a diameter limit has been assumed based on surveyor instructions (e.g., 12.7 cm [5 inches]; 1833 instructions—Bourdo, 1956; Hanberry, 2021; Hanberry, Yang, et al, 2012; Manies & Mladenoff, 2000; Rhemtulla et al, 2009; White, 1983) or reported diameters (e.g., 5–15 cm [2–6 inches]; Bourdo, 1956; Cottam & Curtis, 1949; Grimm, 1984; Liu et al, 2011; Williams & Baker, 2011). Unfortunately, these diameter limits are absolute minimums and do not account for selective bias against trees larger than that limit.…”
Section: Methodsmentioning
confidence: 99%
“…These records contain substantial surveyor choice compromising any calculation of species composition, tree density, or size frequency distribution from them (cf. Almendinger, 1996; Grimm, 1984; Hanberry, 2021; Kronenfeld, 2014; Liu et al, 2011).…”
Section: Determination Of Surveyor Biasesmentioning
confidence: 99%
“…Forest disturbances either human-induced or natural have the potential to shape forest systems by altering composition, structure, and functional processes [8] [9] [10] [11]. Human induced forest disturbances are multifaceted and include conversion to agricultural use, logging and other extractive wood uses, forest fires, hunting and illegal wildlife trade, fragmentation, species invasion, altered bio-geochemical cycles and climate change [12] [13] [14] which leads to deforestation and forest degradation [15].…”
Section: Introductionmentioning
confidence: 99%